Training needs and curriculum of continuing medical education among general practitioners in Tibet, China: A cross-sectional survey - Kang An; Lin Zhang; Runjuan Qiao; Caizheng Li; Qian Zhong; Yiru Ma; Xin Rao; Tingrui Mao; Feng Liu; Qiang Zhuo; Yi She; Yi She; et al. (Frontiers Media S.A., 2022)
BackgroundUneven distribution of health resources is higher in Tibet than in other regions. The development of core professional capability for general practitioners (GPs) is the main goal of continuing medical education (CME) training programs.AimThis study aimed to explore the needs of CME for GPs and provide advice for the development of policy, practice, and CME curriculums.MethodsWe conducted a cross-sectional online survey among GPs in Tibet Autonomous Region, China. We designed an online questionnaire including the demographic section, training contents, and training formats about CME.ResultsA total of 108 questionnaires were included in this study. Notably, 79 (73.15%) were women and 56 participants (51.85%) were working in primary care settings. We developed a curriculum priority: first-choice, major alternatives, and secondary considerations. The topics identified as first-choice for CME were related to "cardiovascular disease" (85.19%), "respiratory disease" (81.48%), and "digestive disease" (80.56%). Major alternatives included two essential knowledge and eight clinical skill items. We rated 10 items as secondary considerations. Only 39.81% ranked mental health as an essential priority; bedside teaching (51.85%) was the first choice.ConclusionWe presented priority areas identified in this study to focus on CME for GPs in Tibet. The 23 topics may reflect the features of general practice, which increasingly require common disease management skills, while a demand-oriented curriculum and staged training plans should be adopted. CME programs should be adapted dynamically to respond to evolving needs.